(Very) long‐term transport of Silurus glanis, Carcharhinus melanopterus, Scomber colias, Trachurus picturatus, Polyprion americanus, Rhinoptera marmoratus, Salmo salar, Scomber scombrus, Sardina pilchardus, and others, by land, water and air. Issue 6 (9th February 2022) - Correia, João; Daghfous, Gheylen; Silva, David; Graça, Gonçalo; Beltran, Ivan; Reis, João; Marques, José P.; Silva, Luís; Guedes, Rui; Morato, Telmo
Abstract: In this paper, we cover 4 years of live fish transports that ranged from 14 to 200 h (8 days), and bioloads from 3.8 to 76.9 kg/m 3 . The key ingredients for success in all trips, where virtually no mortality occurred, was atributed to (1) pre‐buffering the water with sodium bicarbonate and sodium carbonate at 50 g/m 3 (each)—and/or ATM Alka‐Haul TM at 25 g/m 3 —and applying additional (partial or full) doses throughout each transport, whenever the tanks were accessible; (2) pre‐quenching ammonia with ATM Triage TM at 32 g/m 3, and applying additional (partial or full) doses throughout each transport, whenever the tanks were accessible; (3) keeping the dissolved oxygen saturation rate above 100%, ideally above 150%; (4) Keeping temperature on the lower limit of each species' tolerance range; (5) Using foam fractionators to effectively eliminate organic matter from the water and (6) Using pure sine wave inverters, which allows for a steady supply of electrical current throughout the transport. The use of a 'preventive' versus 'corrective' pH buffering philosophy is also discussed. Abstract : pH in all four tanks loaded with 300 Salmo salar smolts (each), which travelled from Sveio (Norway) to Aveiro (Portugal) over 72 h (3 days), including the addition of pH buffers, which were identical in all 4 tanks. Note the stability of pH from 38 h of transport onwards, thanks to the 'predictive' addition of sodium bicarbonate, instead of 'corrective'. Highlights: We cover 4 years of live fish transports that ranged from 14 to 200 h, and bioloads up to 76.9 kg/m 3 . Key ingredients of success were pH buffering, ammonia quenching, high D.O., low temperature, foam fractionators, pure sine wave inverters.